Humanización de la Arquitectura Hospitalaria Pautas de diseño, para el bienestar emocional y recuperación del paciente. - Rubio Ancajima, Angel Nicolas (2026)
The humanization of hospital architecture represents a conceptual revolution in architecture, incorporating design guidelines centered on the diverse needs of its users. This research analyzes how factors of the built environment—natural light, biophilic design, acoustic comfort, appropriate colors, warm materials, and architecture conducive to human dignity—influence outcomes for the emotional well-being and recovery of patients, families, and healthcare staff. In this context, humanization, based on architectural design guidelines, emerges as a key concept for improving the hospital experience, reducing stress, and promoting patient recovery. This article aims to analyze the relationship between hospital architecture and user well-being, identifying design guidelines that contribute to the creation of therapeutic, emotional, and recovery environments. The research is developed from a theoretical and conceptual review based on contributions from architecture, environmental/architectural psychology, and user-centered design. The results of the analysis demonstrate that hospitals designed according to human-centered design principles offer significant benefits for both patients and healthcare staff by promoting more comfortable, accessible, and emotionally positive spaces. Furthermore, the incorporation of strategies such as natural lighting, thermal comfort, indoor environmental quality, and the integration of nature into the interior contributes to reducing stress and improving the hospital experience. In warm climates, such as that of Piura, these strategies become even more relevant, solidifying passive design as an efficient and sustainable solution. It is concluded that hospital architecture, when it prioritizes spatial quality and the human dimension, becomes an active component of the healthcare process, and that the humanization of hospital architecture should be understood as an integral design principle, incorporated from the initial stages of the architectural project, and not merely as an aesthetic resource.